Assisted hatching - should we keep doing it? - Zion Ben Rafael; Mordechai Ben David (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2022)
Assisted Zona Hatching (AZH) like most add-ons was introduced to In Vitro Fertilization and Embryo transfer (IVF/ET) in the early 1990s, when the live birth rate (LBR) in older women, age 35-39, was only 6%.